The Role of Metacognitive Strategies in English Reading Classes - Magdalena Kartikasari Tandy Rerung (Journal of English Language and Culture, 2017)
The following study is intended to find out which is the highest use of metacognitive reading strategies among the academic learners majoring in English Language and Culture, Bunda Mulia University Jakarta. First of all metacognition discusses the process of an individual in planning and managing oneself in order to achieve his or her goal. In the other words, metacognitive strategies are steps that learners take for improving their language performances. Based on SORS (Survey of Reading Strategies) questionnaire, there are four categories being scored in the reading metacogntive strategies. They are global reading strategies, problem-solving strategies,, and support reading strategies. The result showed that academic learners mostly apply the problem-solving strategies, followed by global reading strategies, and support reading strategies.         Keywords: Metacognitive, Strategies, Reading Classes